Efficacy and harms of pharmacological interventions for neurobehavioral symptoms in post traumatic amnesia after traumatic brain injury: a systematic review and meta-analysis protocol. (December 2017) - Hicks, Amelia J.; Clay, Fiona J.; Hopwood, Malcolm; Jayaram, Mahesh; Batty, Rachel; Ponsford, Jennie L.
Abstract : Review objective/question: The objective of this systematic review is to synthesize the best available evidence on the effectiveness and harms of pharmacotherapy as compared to all types of comparators for the management of neurobehavioral symptoms in post-traumatic amnesia in adults aged 16 years and over who have sustained a traumatic brain injury. This review forms part of a larger project which aims to gather the evidence for the pharmacological treatment of neurobehavioral symptoms post traumatic brain injury as a prelude to the development of a clinical guideline.